TAX AWARENESS AS MODERATOR TOWARDS TAX KNOWLEDGE, SUBEJCTIVE NORMS, PERSONAL NORMS, AND TAX COMPLIANCE - Tessya Adellia; Imas Nurani Islami (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2020)
The development and quality improvement of public service is highly relying on funding from taxation. However, tax compliance is still low in Indonesia. The purpose of this research is to investigate whether subjective norms, personal norms, and tax knowledge have positively influence to taxpayer compliance and whether those factors of tax compliance is moderated by tax awareness. The researcher used electronic questionnaire to distribute questionnaire to respondents domiciled in Cikarang. The minimum samples taken in this research are 135 and 174 questionnaires are eligible. Statistical analysis used in this research is Structural Equation Modeling (SEM). The results show that subjective norms has directly insignificant influence to taxpayer compliance. Furthermore, personal norms and tax knowledge have directly significant influence to tax compliance. On the other hand, subjective norms are not moderated by tax awareness to tax compliance. Personal norms and tax knowledge are moderated by tax awareness to tax compliance.  The implication of this study is that the level of taxpayer compliance should be put into account and be improved. According to the result of this research, level of taxpayer compliance may give a positive effect to ease the amount received from tax and report the tax return.